Negotiating under Political Uncertainty: National Elections and the Dynamics of International Co-operation. Issue 1 (6th February 2017) - Kleine, Mareike; Minaudier, Clement
Abstract : This article explores if (and how) national elections affect the chances of concluding an international agreement. Drawing on a literature about the informational efficiency of elections, it examines how political uncertainty in the run-up to an election impacts the dynamics of international negotiations. Using the case of decision making in the European Union (EU), it finds that (1) pending national elections significantly reduce the chances of reaching an agreement at the international level (2) this effect is strongest during close elections with uncertain outcomes and (3) the effect is particularly pronounced in the case of elections in larger member states. The findings highlight the fruitfulness of further research on the dynamics between national and international politics. The article has positive and normative implications for the literature on two-level games, international negotiations and legislative bargaining in the EU.